Isolation of verotoxin-producing Escherichia coli associated with diarrhoea in Malaysia containing plasmids showing homology with biotinylated Shiga-like toxin DNA gene probes - Radu, Son; Ansary, A.; Rahmat Ali, Gulam Rusul; Abdul Karim, Mohamed Ismail (Rapid Science Publishers, 1996)
Three strains of verotoxin-producing Escherichia coli isolated from patients with haemorrhagic colitis harboured plasmids ranging in size from 2.7 kb to 91.2 kb. Those plasmids ranging from 2.7 kb to 6.8 kb hybridized to Shiga-like toxin I and Shiga-like toxin II gene probes.